As reminiscências de um educador vitorioso - Pereira, Elias da Silva (Brasil, 2024)
The present work aims to present the memorial that will expose the entire path I have taken in education and the three supervised internships, with periods of observation and classroom work. Addressing relevant points during my career at the beginning of my school education, teaching and the periods in which supervised internships took place, covering observations and guidance, in early childhood education, the initial years of primary education and school management. Using bibliographic research as methodological requirements, with a qualitative approach. The course's final conclusion work is divided into three chapters entitled: chapter one – From the first steps in education to entry into teaching, chapter two – Academic training in pedagogy and chapter three – Experiences, teaching practices and school management.